Русские в горном Алтае: хозяйственное освоение новых территорий (конец XVIII – начало XX вв.) - Shietova, N. I.; Шитова, Н. И. (Издательство Тюменского государственного университета, 2016)
The most part of the research is based on field ethnographic materials of the author and on narrative sources. Landscapes in Gorny Altai are represented by the following types: low-mountains area, mid-mountains area and high mountains area. The author sets the task to study specific features of the land is development in the particular zones by the Russian population: in the low-mountains zone (Maima, Choya, Turochak Districts), mid-mountains zone (Chemal, Shebalino, Ongudai, Ust-Kan Districts) and high-mountains zone (Ust-Koksa District). The development in high- and mid-mountains zones is mainly presented by cattle farming, whereas agriculture has taken the second place. It is important to note that the most success in crop farming has been achieved by residents at the Uymon Depression (high mountains) and at the Charysh Valley (mid-mountains). The amount of agriculture’s crops in the most of the districts in mid- and low-mountains zones were not enough for cooking Russian traditional meals (dishes prepared out of flour and grain). The people had to compensate the lack of it by bread, taken from other territories, and by essential amount of animal products. People used to receive “bread” from the Altai steppes in exchange of products of cattle farming, forest husbandry and bee keeping. The residents at low mountains, especially at places with taiga (Turochak and Choya Districts), were most dependent on this exchange. The natural conditions were least suitable for agriculture and even for cattle farming at these lands. That is why people developed forest husbandry and hunting more. As a result of the land is development by the Russians in the studied region, the natural conditions played a significant factor in forming a specific balance between cattle farming and forest husbandry, which became the basic activities in the economy, on the one hand, and agriculture and other activities of the secondary value, on the other hand. Исследуется процесс освоения новых земель русскими в горном Алтае в конце 18 – ...